Knygų hebrajų ir jidiš kalbomis fondai Lietuvoje - Zingeris, Emanuelis (Knygotyra, 1987)
The matter of author’s concern are the Jewish book stocks in the book depositories of the Lithuanian libraries. What is the criterion of rare Jewish books in Lituania, what is the role of these books in the relations of the Jewish-Lithuanian cultures?To help the librarians to classify Jewish books, the main Jewish writers and literary trends, historically significant works are named. The author is presenting some rare historical data about the famous Jewish printing houses and libraries. He also deals with the question of Jewish rarities transported to Germany during the II-nd World War. Despite the heroic struggle of intellectuals in Vilnius ghetto to preserve the Jewish cultural inheritance, the Baltic branch of Einsatzstab of Reichsleiter Rosenberg managed to anihilate a great part of these rarities. Just during one “action” in 1942, the Germans have transported about 20 000 books to Frankfurt a. M and annihilated 80 000 in the paper-mills in Vilnius. The greater part of these books bearing the stamps of Lithuanian Jewish libraries still are in various book depositories of Frankfurt a. M. Some non-Jewish intelectuals took an active part in saving the Jewish books from distruction. The brief survey of the Jewish book-stocks in various depositories in Lituania concludes the article.The author dedicates his work to Antanas Ulpis (1904–1981), the pased director of the Book Chamber of the Lithuanian SSR, who did much to collect and preserve Jewish books in the years after the II-nd World War. A. Ulpis helped to restore the Jewish and Hebrew book-despositories in Lithuania, published during the XIX and the 1st half of the XX century.The cultural inheritance of the Lithuanian Jews is an invaluable material for scholars studying the multinational culture of Lithuania.